A case of Type-C Wolff–Parkinson–White syndrome with severe left ventricular dysfunction: Efficacy of catheter ablation. Issue 1 (January 2017) - Haraguchi, Miho; Kondo, Hidekazu; Ishii, Yumi; Kobukata, Mami; Imamura, Takaaki; Otsubo, Toyokazu; Ayabe, Reika; Saito, Shotaro; Nagano, Yasuko; Akioka, Hidefumi; Shinohara, Tetsuji; Teshima, Yasushi; et al.
Abstract: The present case report describes a 59-year-old female with manifest Wolff–Parkinson–White syndrome and severe left ventricular (LV) dysfunction, however, there was no indication of heart palpitations. The polarity of delta is consistent with the features of the right anteroseptal accessory pathways (APs). The echocardiography showed a remarkable dyssynchrony of the LV wall motion. To circumvent the cardiac dysfunctions, radiofrequency catheter ablation (RFCA) was successfully performed to disconnect the AP. Thereafter, the dyssynchrony disappeared, and the clinical reports observed 6 months following RFCA showed that the LV ejection fraction had been improved from 13% up to 48%, in addition to the improvement in other parameters. The RFCA prevented her from receiving a cardiac resynchronization therapy defibrillator as well as a heart transplantation. <Learning Objective: There is a concern about the possibility that some patients with Wolff-Parkinson-White (WPW) syndrome and heart failure may be diagnosed with dilated cardiomyopathy (DCM). Because catheter ablation of the accessory pathway may improve the left ventricular (LV) dysfunction, one should exclude the accessory pathway conduction-induced LV dyssynchrony and LV dysfunction before diagnosing DCM. Even in absence of palpitations, catheter ablation may be effective in patients with manifest WPW syndrome to prevent the progression of LV dysfunction.>